2021
DOI: 10.3390/ijerph18052542
|View full text |Cite
|
Sign up to set email alerts
|

Concerns or Desires Post-Pandemic: An Extended MGB Model for Understanding South Korean Residents’ Perceptions and Intentions to Travel to China

Abstract: In this study, we examined South Korean residents’ travel-related behavioural intention for mainland China post-COVID-19 using an extended model of goal-directed behaviour. To do so, we integrated South Korean residents’ perceptions of country image (PCI), mass media, and concerns about travel into the framework of the original model of goal-directed behaviour (MGB). Structural equation modelling was used to identify the structural relationships among the latent variables. The results show that mass media had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In line with these findings, previous studies [24,25,30] demonstrated that stronger positive emotions (e.g., emotional solidarity) explained individuals' increased willingness to engage in more intimate interactions (i.e., affinity) with others. Consistent with previous studies carried out by Qiao et al [47] showing that residents' negative anticipated emotions lead to a lower desire to travel, and Thyne et al [30], reporting that residents' negative perceptions of tourism increased their perceptions of social distance (less intimate-distal and more intimate-proximal) with tourists, the present study revealed that accommodating emotions was a negative significant predictor of both degrees of intimate activities (H 11 and H 12 ).…”
Section: Discussionsupporting
confidence: 91%
“…In line with these findings, previous studies [24,25,30] demonstrated that stronger positive emotions (e.g., emotional solidarity) explained individuals' increased willingness to engage in more intimate interactions (i.e., affinity) with others. Consistent with previous studies carried out by Qiao et al [47] showing that residents' negative anticipated emotions lead to a lower desire to travel, and Thyne et al [30], reporting that residents' negative perceptions of tourism increased their perceptions of social distance (less intimate-distal and more intimate-proximal) with tourists, the present study revealed that accommodating emotions was a negative significant predictor of both degrees of intimate activities (H 11 and H 12 ).…”
Section: Discussionsupporting
confidence: 91%
“…COVID-19-related anxiety symptoms have been noted (Luo & Lam, 2020;Zenker et al, 2021). In tourism, anxiety may stem from various sources like socio-cultural, terrorism, health, or financial concerns, leading to reduced travel motivation (Chua et al, 2021;Qiao et al, 2021;Reisinger & Mavondo, 2005). Research indicates that the pandemic's risk perception has had negative effects on travel intentions, often driven by anxiety (Chua et al, 2021;Luo & Lam, 2020;Quintal et al, 2022;Zheng et al, 2022;Zenker et al, 2021).…”
Section: B Social Media Impactmentioning
confidence: 99%
“…Previous studies illustrated the need of conjoint efforts from governments, health professionals and local communities in the construction of open communications, public health infrastructures and capabilities to provide in-time response and measures in dealing with global health emergencies. These measures included testing, sanitation, social distancing and mobility tracing (Qiao, Zhao, Xin, & Kim, 2021;V arzaru, Bocean, & Cazacu, 2021;Villac e-Molinero, Fern andez-Mun ˜oz, Orea-Giner, & Fuentes-Moraleda, 2021).…”
Section: Prevention Measures Under the Pandemic Backdropsmentioning
confidence: 99%